A Formative Conceptual Framework On Models Of Teaching Strategies In Fashion Design Course - Raja Shahriman, Raja Iskandar Shazrim Shah; Shaari, Nazlina (2016)
The purpose of this paper is to provide a formative analysis of conceptual framework on the study of design pedagogy and models of teaching strategies applied by fashion expert tutors, particularly on novice fashion design students within noted public and private institutions of Klang Valley. This research employed a comparative study approach on models of teaching strategies, with a purpose to look into the pros and cons associated with different teaching techniques employed upon novice students. Samples of this study consist of fashion expert tutors, who are currently teaching design-clustered subjects offered within fashion courses. Concurrently, a selected number of established and noted fashion designers were also conferred on to provide invaluable insights towards the issues. The result of the study suggests a set of research keywords that were then subsequently provide significant data during further critical analysis on the collective models of teaching strategies employed during interviews. The findings suggest a formative conceptual framework where such research can be further developed in the implementation process of a concise model of teaching strategies, able to be applied by both experience and inexperience fashion design tutors within their pedagogical practices. A developmental model that would enhance designs learning experience and student skills acquisition time. Developing adequate skills fit for the industry and conforms to fashion standard practices. This study conducted to initiate further research and development in the models of teaching strategies of fashion design tutors, which could enhance the learning process of novice students. Contribute in the encouragement of positive developments in the curriculum design, which helps to assist student individuals and industrial key players. Local higher education providers, which then may accede to implement the findings of this study and improvise the pedagogical practice of fashion design education. Hence, contribute positively in the educational practices of the ever-challenging fashion design industry